Promiscuous Dimerization of the Growth Hormone Secretagogue Receptor (GHS-R1a) Attenuates Ghrelin-mediated Signaling - Schellekens, Harriët (American Society for Biochemistry and Molecular Biology, 2013)
G protein-coupled receptors (GPCRs), such as the ghrelin receptor (GHS-R1a), the melanocortin 3 receptor (MC(3)), and the serotonin 2C receptor (5-HT(2C)), are well known for their key role in the homeostatic control of food intake and energy balance. Ghrelin is the only known gut peptide exerting an orexigenic effect and has thus received much attention as an anti-obesity drug target. In addition, recent data have revealed a critical role for ghrelin in dopaminergic mesolimbic circuits involved in food reward signaling. This study investigates the downstream signaling consequences and ligand-mediated co-internalization following heterodimerization of the GHS-R1a receptor with the dopamine 1 receptor, as well as that of the GHS-R1a-MC(3) heterodimer. In addition, a novel heterodimer between the GHS-R1a receptor and the 5-HT(2C) receptor was identified. Interestingly, dimerization of the GHS-R1a receptor with the unedited 5-HT(2C)-INI receptor, but not with the partially edited 5-HT(2C)-VSV isoform, significantly reduced GHS-R1a agonist-mediated calcium influx, which was completely restored following pharmacological blockade of the 5-HT(2C) receptor. These results combined suggest a potential novel mechanism for fine-tuning GHS-R1a receptor-mediated activity via promiscuous dimerization of the GHS-R1a receptor with other G protein-coupled receptors involved in appetite regulation and food reward. These findings may uncover novel mechanisms of significant relevance for the future pharmacological targeting of the GHS-R1a receptor in the homeostatic regulation of energy balance and in hedonic appetite signaling, both of which play a significant role in the development of obesity.